Implementation of Ta'dib Values in Forming Noble Morals in Islamic Religious Education Learning - Hanif Najmi; Hafidz; Bagas Faiz Rizky; Nuzulia Mustika Dhani; Isnadia Wilda Hanifah; Dina Arifatul Husna; Eka Febriyani; Nadhira Naura Rezelia (Bulletin of Islamic Research, 2025)
Islamic education aims to form individuals who have a balance in intellectual, emotional, behavioral, and spiritual aspects comprehensively. However, in its implementation in the field, Islamic education faces various challenges, especially in the process of transmitting knowledge and instilling Islamic values. These problems include a lack of a thorough understanding of the concept of Islamic education, limited resources, and resistance to Islamic approaches in the modern environment. This study uses a qualitative method with a descriptive-analytical approach to examine the relevance of the concept of ta'dib as initiated by al-Attas in Islamic education. Data were obtained through in-depth interviews with practitioners and education observers, direct observations, and literature studies of al-Attas' works and related documents. Content analysis techniques are used to evaluate the challenges of Islamic education and identify how the concept of ta'dib can be applied practically. The results of the study show that the concept of ta'dib is relevant as a comprehensive model of Islamic education. This approach emphasizes the importance of an Islamic view of life through the integration of tawhidy values in every aspect of the educational process. With the application of the concept of ta'dib, Islamic education has the potential to create civilized humans who are able to provide solutions to the problems of the people, although systematic efforts are still needed to overcome implementation challenges in the field.